Systematic Review: Association of Pesticide Exposure and Child Wheeze and Asthma - Gilden, Robyn C.; Harris, Ryan L.; Friedmann, Erika J.; Han, Myeunghee; Hackney, Alisha J.; Olorunyemi, Emmanuel; Spanier, Adam J. (Current Pediatric Reviews, 2023)
Background: The prevalence of wheeze and asthma has risen over recent decades for all age groups, especially children. These disorders can lead to decreased quality of life, missed school, urgent care and emergency department visits, hospitalizations, and increased health care costs. Environmental exposures, including pesticide exposure, are likely a contributing factor to this increased prevalence. Objective: To evaluate the association of pesticide exposure with childhood wheeze and asthma. Methods: We conducted a systematic review evaluating studies of pesticide exposure (measured objectively) and child respiratory outcomes. We searched PubMed, Embase (Elsevier), CINAHL (EBSCO), Scopus (Elsevier), Cochrane Database of Systematic Reviews (Wiley), and ClinicalTrials. gov from 1988 - 2021. Main search keywords included “pesticides”, “insecticides”, “herbicides”, “respiratory”, “asthma” and “wheeze”. Results: Out of 5767 studies, 25 met the inclusion criteria; eight evaluated prenatal pesticide exposure (n=8407), twelve evaluated postnatal exposures (n= 50,488), and five evaluated pre-and postnatal exposures (n=20,919). Main pesticides investigated were dichlorodiphenyldichloroethylene (DDE) (14 studies) followed by organophosphates (7 studies). Primary methods of outcome assessment were questionnaire-based (84%), followed by spirometry (16%), registry data, and blood measures. Studies varied in the strength of evidence relating to study design and measures. Most studies (84%) reported a positive association of exposure with adverse child respiratory health. Conclusion: The studies suggest an association of pesticide exposure and childhood wheeze and asthma. The varying results and methods reinforce the need for more research and standardized approaches to these studies to confirm the suggested association of pesticide exposure and childhood wheeze and asthma.
Keywords: postnatal